Penerapan Model Pembelajaran Student Teams Achievement Division (STAD) Untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas Iii Berbantuan Media Human Clock - Linda Mayangsari; Pinkan Amita Tri P; Sri Sujanti (Journal on Education, 2024)
This research aims to overcome the problems that exist in class 3B of SDN 02 Mojorejo, Madiun City, namely the low student learning outcomes in mathematics subjects measuring units of time. This research design uses the Kemmis and Mc Taggart model with stages of planning, implementation, observation and reflection carried out through two cycles. Data analysis techniques were carried out descriptively and qualitatively. The research results show that mathematics learning using the Student Team Achievement Division (STAD) model assisted by human clock media can be carried out in accordance with the steps in the Learning Implementation Plan (RPP), students become more orderly and organised, active and enthusiastic in the learning process. The learning outcomes obtained by students also increased, namely from 25 students the average score for pre-action learning outcomes was 67.6%, then in cycle 1 it became 74% and cycle 2 increased to 92%, so it can be concluded that the use of the STAD model with the help of human clock media, it can improve the mathematics learning outcomes of class 3B students in time unit measurement material at SDN 02 Mojorejo, Madiun City.